The Influence of Multinational Workforce Diversity and Organizational Culture on Employee Performance at PT Q Qatar - Nugroho, Yuniarko; Hasbi, Hariandy (Dinasti Publisher, 2026)
This study aims to analyze the influence of multinational workforce diversity and organizational culture on employee performance at PT Q Qatar, a company characterized by its cross-cultural workforce. Multinational workforce diversity reflects the extent to which employees of different nationalities, ethnicities, religions, and cultural backgrounds are managed fairly and inclusively. Meanwhile, organizational culture represents the shared values, norms, and behaviors that shape work patterns and social relationships within the company. This research employs a quantitative approach using a survey method conducted on 150 respondents selected proportionally from various departments. Data were collected through a five-point Likert scale questionnaire and analyzed using PLS - Structural Equation Modeling. The results reveal that multinational workforce diversity has a positive and significant effect on employee performance, indicating that inclusively managed diversity enhances collaboration and productivity. Organizational culture also shows a positive and significant influence on employee performance, suggesting that a strong and adaptive culture fosters a harmonious and effective work environment. This study underscores the importance of implementing effective diversity management practices and strengthening organizational culture to improve performance in multinational companies such as PT Q Qatar.